2016
DOI: 10.1103/physrevb.94.024105
|View full text |Cite
|
Sign up to set email alerts
|

Octahedral rotation patterns in strainedEuFeO3and otherPbnmperovskite films: Implications for hybrid improper ferroelectricity

Abstract: We report the relationship between epitaxial strain and the crystallographic orientation of the inphase rotation axis and A-site displacements in P bnm-type perovskite films. Synchrotron diffraction measurements of EuFeO3 films under strain states ranging from 2 % compressive to 0.9 % tensile on cubic or rhombohedral substrates exhibit a combination of a − a + c − and a + a − c − rotational patterns. We compare the EuFeO3 behavior with previously reported experimental and theoretical work on strained P bnm-typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 74 publications
3
5
0
Order By: Relevance
“…Particularly, the Berry curvature and the resulting anomalous Hall conductivity vary non-monotonically with increasing θ. Previous experiments have demonstrated that external strain modulation can control octahedral rotations in oxide thin films [43,44]. Our presented results, therefore, show an effective way to control the Berry phase and consequently the topological properties of perovskite transition-metal oxides by epitaxial strain engineering.…”
supporting
confidence: 60%
“…Particularly, the Berry curvature and the resulting anomalous Hall conductivity vary non-monotonically with increasing θ. Previous experiments have demonstrated that external strain modulation can control octahedral rotations in oxide thin films [43,44]. Our presented results, therefore, show an effective way to control the Berry phase and consequently the topological properties of perovskite transition-metal oxides by epitaxial strain engineering.…”
supporting
confidence: 60%
“…These atomic density changes boost the enhancement of the relative oxygen/cation contrast; therefore, under the premise of high spatial resolution in a Cs-corrected STEM, the <110> pc zone axis provides a better contrast of the oxygen columns than the <100> pc zone axis. Moreover, considering the characteristics of in-plane oxygen octahedral rotation, such as in the case of a − a − c + (following Glazer’s notation41) in orthorhombic LSMO (space group Pnma )42, the anti-phase rotation in the <100> pc zone axis introduces a split of the oxygen columns, thus blurring and eclipsing the oxygen atomic propagation, while the in-phase rotation in the [1–10] pc zone axis gives a sharp propagation. Accordingly, the [1–10] pc zone axis was selected in our work for an enhanced contrast of the oxygen and in-phase octahedral rotation in each LSMO monolayer of the heterostructures (a detailed quantitative ABF intensity analysis can be found in the supporting information Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, there is a symmetry misfit arising from NiO 6 -octahedral tilts (rotations) in NNO. Such a symmetry misfit is typical for the epitaxy of orthorhombic perovskites on square surfaces of versatile substrates [10][11][12][13]. The symmetry misfit relaxes within a few nanometers near the film-substrate interface, as was evidenced by the evolution of tilts towards bulklike patterns in nickelates [11,[14][15][16].…”
Section: A Film Structurementioning
confidence: 92%